EFFECT OF ETHANOL EXTRACT OF BHEE FRUIT (MELASTOMA SP) ON CHOLESTEROL LEVELS IN DIABETIC MICE - Mhd. Hermanda Syahputra; Rinawati; Suci Eka Putri; Cukri Rahma (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Diabetes mellitus is a chronic disease that causes death. Diabetes is associated with increased total cholesterol levels. Insulin resistance causes glucose levels to increase in the blood and inhibits the circulation of food juice. The body will break down fat as an energy source due to glucose that cannot reach the body's cells, this causes an increase in cholesterol levels in the blood. Several studies have shown a correlation between increased blood glucose levels and increased cholesterol levels. Control of blood glucose levels in diabetics should be done so as not to cause an increase in blood cholesterol. Herbs are chosen as an alternative for antidiabetics. Bhee fruit (Melastoma Sp) has the potential to an antidiabetic because of its phytochemical content. In West Aceh, there has not been much research on diabetes herbal medicine and the use of Bhee Fruit as an herbal medicine. The purpose of this study was to determine the effect of ethanol extract of Bhee fruit on total cholesterol levels of alloxan-induced diabetic mice. Method: Laboratory experimental research with Complete Randomized Design (RAL) using 21 mice divided into 7 treatments namely KN, KP, KO, KD, P1, P2, and P3. Measurement of cholesterol levels using easy touch tools and Cholesterol strips. The dose of ethanol extract of Bhee fruit used is 100, 200, and 400 mg/kg body weight and given for 14 days. Data analysis was performed using One-way ANOVA and followed by the Duncan Analysis test. Results: Giving ethanol extract of Bhee fruit at doses of 100, 200, and 400 mg / dL was able to reduce total cholesterol levels in diabetic mice. Conclusion: Giving Bhee fruit extract affects reducing total cholesterol levels, with a dose of 400 mg/kg body weight which is most effective in reducing total cholesterol levels in diabetic mice. Suggestion: it is necessary to do further tests using different types of solvents and different doses.